Population structure of giant clams (tridacnidae) in Aceh Besar district waters - M Rizki Fazillah; Chitra Octavina; Muhammad Agustiar; Muhammad Akhyar (Tomini Journal of Aquatic Science, 2020)
Giant clams have an essential ecological role in the coral reef ecosystem. Given the decreasing number of giant clams in nature, the status of giant clams as protected animals, and there is still little information about giant clams, data or information is needed to make policies regarding giant clam conservation management. This study aimed to determine the population structure of giant clams (Tridacnidae) in the coral reef area of Aceh Besar District. The research was conducted in May 2018, located in Aceh Besar Regency waters with six observation stations. Observation of giant clams is carried out using a visual census technique with the belt transect method. The observations showed that the giant clams found in Aceh Besar waters consisted of 2 species, namely Tridacna maxima and Tridacna crocea. Overall stations, the individual density of giant clams is 0.041 ind. m-2. The diversity index of giant clams shows a value ranging from 0–0.97, classified in the low diversity category. The similarity index value of giant clams is classified into the stressed to stable similarity category with values ranging from 0–0.97. The dominance index value of giant clams is classified in the medium to high dominance category with values ranging from 0.52 to 1. The distribution pattern of the two giant clam species found in the waters of Aceh Besar District has a uniform distribution pattern with values ranging from 0.20–0.29. The overall population structure of Tridacnidae is in unstable condition.